Efecto de la metformina en la mucosa bucal en Rattus rattus var. albinus - Almeida Alvarado, Adrián Enrique (2017)
The aim of the present study was to identify the effect of metformin on the buccal mucosa in Rattus rattus var. Albinus in cheeks and Hard Palate. For this the histological sections of Rattus rattus with Gomori staining and haematoxylin of Harris and Eosin were compared, which were submitted to an experimental study being separated in control group that were administered via gastric probe to a volume of 3% of the body weight Of physiological saline solution (SSF) for 14 days and a problem group that was administered via gastric gold probe a volume of 3% of body weight concentrations of 500mg / kg Metformin dissolved in SSF for 7 days and later the dose of Metformin 750mg / kg for the remaining 7 days. The results show that metformin does not produce alterations at the hard palate level and in 20% of the Rattus rattus study acute inflammation was found given the following characteristics as mucosal ulceration compromising the epithelium, hyperplasia with epithelial hyperkeratosis, thickening Of the wall of small and medium blood vessels in submucosa, dilation of blood vessels in lamina propria and fibrous hyperplasia of connective tissue in lamina propria. In this study, tissue-grade damage to Rattus rattus cartilage was found to be due to the use of metformin. El objetivo del presente fue identificar el efecto de metformina en la mucosa bucal en Rattus rattus var. Albinus en carrillos y Paladar Duro. Para esto se han comparado los cortes histológicos de Rattus rattus con tinción de Gomori y hematoxilina de Harris y Eosina, que fueron sometidas a un estudio experimental siendo separadas en grupo control que se les administró vía sonda oro gástrica un volumen del 3% del peso corporal de solución salina fisiológica (SSF) por 14 días y un grupo problema que fue administrado vía sonda oro gástrica un volumen del 3% del peso corporal de concentraciones de 500mg/kg Metformina disuelta en SSF por 7 días y posterior se le aumento la dosis de la Metformina 750mg/kg durante los 7 días restantes. Los resultados muestran ...